2022
DOI: 10.3389/fped.2022.841582
|View full text |Cite
|
Sign up to set email alerts
|

Does Learning Through Movement Improve Academic Performance in Primary Schoolchildren? A Systematic Review

Abstract: Physically active children have greater motor competence and a faster maturation compared with their sedentary peers. Recent research also suggests that physical activity during childhood may also promote cognitive development and therefore improve academic performance. The aim of this study was to understand if physically active academic lessons may improve academic achievement in primary schoolchildren. A systematic review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…Therefore, the approach taken in many intervention programs is to use external sports coaches to teach the physical education classes [59]. Previously, the concept of teaching cognitive content in combination with movement and PA was used, in particular in mathematics and language learning, as in our intervention, and led to an improvement in the cognitive performance of the participating children [60,61]. Other intervention designs prefer to organize additional sports activities in the school settings outside of class time [59], adding an additional daily physical activity lesson to the curriculum [30,32,62], spending the daily morning break at school with physical activities [63], or implementing high-intensity physical activity programs during short breaks in cognitive lessons [64].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the approach taken in many intervention programs is to use external sports coaches to teach the physical education classes [59]. Previously, the concept of teaching cognitive content in combination with movement and PA was used, in particular in mathematics and language learning, as in our intervention, and led to an improvement in the cognitive performance of the participating children [60,61]. Other intervention designs prefer to organize additional sports activities in the school settings outside of class time [59], adding an additional daily physical activity lesson to the curriculum [30,32,62], spending the daily morning break at school with physical activities [63], or implementing high-intensity physical activity programs during short breaks in cognitive lessons [64].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, integration of physical activities with the teaching curriculum content had been recommended and explored in primary schools (Webster et al 2015;Mavilidi and Vazou 2021). A recent review showed that physically active lessons yielded benefits in motor skills and academic performance among primary school students (Petrigna et al 2022). There has also been evidence that such integrated lessons enhanced students' focus during class, (i.e., time-on-task) which could contribute to academic learning processes (Mullender-Wijnsma et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There has been particular interest with integrating movements with mathematics, as it has been argued that sensorimotor components transform mathematical concepts into tangible events or situations for young children, thereby facilitating effective learning (Mavilidi et al 2018). In relation to health, such integrated approach can increase the amount of physical activity time and help children meet the recommendations to gain associated health benefits (Petrigna et al 2022;Vetter et al 2020). In ECEC settings, this potentially useful strategy may allow teachers to circumvent the challenges associated with promoting physical activity in the face of academic learning requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our hypotheses, the initial level of PA (PA a or PA b ) or the diagnosis of ADHD did not in uence the effectiveness of the intervention. Means, Standard Deviations, and Mean Difference Across Groups for Child Development Domains).DiscussionOver the past few years, there has been a growing interest in school-based PAL programs as promising interventions to increase PA levels among school-aged children and potentially enhance educational outcomes[36, 38,39,41,57]. However, limited knowledge exists regarding the effects of these interventions on holistic child development when implemented in the classroom over an extended period.…”
mentioning
confidence: 99%